The attitude and experiences of high school learners on the teaching of LGBT content in a South African co-ed school - Nichols, Henry James (University of the Free State, 2016)
Upon the ratification of the Constitution, the South African Schools Act of 1996 inaugurated a new education system that confronts all forms of unfair discrimination and intolerance. South African schools, however, remain heteronormative and heterosexist, where many lesbian, gay, bisexual and transgender (LGBT) learners or those who are perceived to conform to non-normative gender and sexual identities, experience heteronormativity and heterosexism daily. Schools and classrooms are spaces where compulsory heteronormative and gender-normative behaviour are tolerated and even promoted. It is in these ‘safe’ and ‘inclusive’ spaces that the LGBT youth encounters physical and emotional harassment. This research study explores high school learners’ attitudes towards, and experiences of the teaching and learning of LGBT issues, and argues that these attitudes and experiences yield rich insights into the possibility to work towards a school climate free of heteronormativity and heterosexism and to create a true ‘safe’ schooling space. Using a case study methodology, semi-structured interviews were conducted with eleven high school learners studying at a co-ed high school in the Gauteng province of South Africa. Findings reveal that high school learners have heteronormative and heterosexist attitudes towards sexual and gender diversity; that sexual and gender diversity is not taught in schools; due to a lack of knowledge, ignorance and stereotyping of gender and sexuality, and that exposure to sexual and gender diversity influences the attitudes of the youth. While the data demonstrates clear evidence of a culture of heteronormativity and heterosexism in high school spaces, it also shows that the youth realises the importance of the teaching and learning of sexuality and gender diversity and want to learn about it. I conclude by calling on schools to invest time in creating policies for safe classrooms and promote critical discussions regarding sexual and gender diversity issues. I also call on teachers to create learning environments where stereotypes and stigmatisations are challenged. Lastly, I acknowledge the limitations of the study.

Met die bekragtiging van die Grondwet, het die Suid-Afrikaanse Skolewet van 1996 ‘n nuwe onderrigstelsel in werking gestel wat alle vorme van onregverdige diskriminasie en onverdraagsaamheid konfronteer. Suid-Afrikaanse skole bly egter heteronormatief en heteroseksisties en baie lesbiese, gay, biseksuele en transgender (LGBT) leerders – of diesulkes wat waargeneem word as nie-norrmatiewe gender – en seksuele identiteit, ervaar heteronormatiwiteit en heteroseksisme op ‘n daaglikse basis. Skole en klaskamers is ruimtes waar verpligte heteronormatiwiteit en gendernormatiwiteit verdra en selfs bevorder word. Dit is in hierdie “veilige” en “inklusiewe” ruimtes waar die LGBT-jeug fisiese en emosionele teistering ervaar. Hierdie navorsingstudie verken die houding van hoërskoolleerders teenoor, en die ervaring van die onderrig en leer van LGBT kwessies en argumenteer dat hierdie houdings en ervarings ‘n ryke insig bied in die moontlikheid om ‘n skoolklimaat vry van heternormatiwiteit en heteroseksisme te skep en dat ‘n werklik “veilige” skoolruimte geskep kan word. Met die gebruik van ‘n gevallestudie metodologie, is semi-gestruktureerde onderhoude met elf hoërskoolleerders in dubbelgeslag skole gevoer in die Gauteng Provinsie van Suid-Afrika. Die bevindings het bewys dat hoërskoolleerders wel heteronormatiewe en heteroseksistiese houdings oor seksuele – en genderdiversiteit het en dat seksuele en genderdiversiteit nie in skole onderrig word nie. As gevolg van ‘n gebrek aan kennis, is onkunde en stereotipering van gender en seksualiteit aanwesig en daardie blootstelling aan seksuele – en genderdiversiteit beïvloed die houdings van die jeug. Alhoewel die data duidelike bewyse toon van ‘n kultuur van heteronormatiwiteit en heteroseksisme in hoërskoolruimtes, wys dit ook dat die jeug die belangrikheid van onderrig en leer van seksualiteit en genderdiverstiteit besef en meer daaroor wil leer. Ek sluit af deur ‘n beroep op skole te doen om tyd te bele in die ontwikkeling van beleide vir veilige klaskamers en om kritiese besprekings aangaande seksuele – en genderdiversiteitskwessies aan te moedig. Ek doen ook ‘n beroep op opvoeders om leeromgewings te skep waar stereotipes en stigmas uitgedaag word. Laastens erken ek die beperkings van die studie.
Dissertation (M.Ed. (Education))--University of the Free State, 2016
Keywords: Bullying; School management and organization; Gender identity